2009
DOI: 10.1055/s-0029-1233486
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Associated with Exercise Training Restores Ventilatory Efficiency in Obese Children

Abstract: The purpose of this study was to test the hypothesis that in obese children: 1) Ventilatory efficiency (VentE) is decreased during graded exercise; and 2) Weight loss through diet alone (D) improves VentE, and 3) diet associated with exercise training (DET) leads to greater improvement in VentE than by D. Thirty-eight obese children (10+/-0.2 years; BMI >95th percentile) were randomly divided into two study groups: D (n=17; BMI=30+/-1 kg/m (2)) and DET (n=21; 28+/-1 kg/m (2)). Ten lean children were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
60
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 29 publications
4
60
0
6
Order By: Relevance
“…[17][18][19][20] Table I contains details of each study, including the country where the intervention was conducted, the focus and duration of the intervention, frequency of sessions, effect sizes for primary outcomes, and study designs. The total number of sessions for the entire duration of the intervention ranged, from 4 to 120 with a median of 41 sessions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[17][18][19][20] Table I contains details of each study, including the country where the intervention was conducted, the focus and duration of the intervention, frequency of sessions, effect sizes for primary outcomes, and study designs. The total number of sessions for the entire duration of the intervention ranged, from 4 to 120 with a median of 41 sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Of the four studies, effect size (Cohen's d) was considered small for one intervention, 20 sufficient for two interventions 17,18 and large for one intervention. 19 Figure 1 depicts the effect sizes for two outcomes. Study execution was based on the number of limitations identified through abstraction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations